Application of sunflower pectin gels with low glycemic index in the coating of fresh strawberries stored in modified atmospheres. (16th April 2021) - Muñoz‐Almagro, Nerea; Herrero‐Herranz, María; Guri, Sonia; Corzo, Nieves; Montilla, Antonia; Villamiel, Mar
Abstract: BACKGROUND: This study reports the use of low glycemic sunflower pectin gel, elaborated with calcium and without or with sweeteners (sucrose, stevia and saccharin) as an edible coating and its possible combination with two modified atmosphere packaging (MAP), in order to extend shelf life, maintaining the quality, of strawberries during the storage at 4 °C. RESULTS: This pectin coating, formed with only calcium and/or stevia or saccharin, extended the shelf life of strawberries with respect to uncoating fruits, up to 12 days, keeping the microbial load constant, the firmness and less weight loss. With the same edible coatings, the shelf life of strawberries was extended up to 23 days when they were combined with MAP [10% carbon dioxide (CO2 ), 85% nitrogen (N2 ) and 5% oxygen (O2 )], maintaining the quality of strawberries, while the other MAP, with a higher CO2 concentration (20% CO2, 75% N2 and 5% O2 ), had no effect. CONCLUSIONS: These results highlight the suitability of the combination of edible pectin coating combined with MAP to obtain an important shelf life extension, maintaining the good quality of the fruit. © 2021 Society of Chemical Industry.